Mekong Routes and Its Role to Vietnamese Buddhism - Nguyen Dat, Ven. Dr. Thich (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 3 No 2 (2020): ปีที่ 3 ฉบับที่ 2 ประจำเดือนกรกฏาคม - ธันวาคม 2563, 2020)
Plato, Greek philosopher, in his influential "theory of Forms", holds that the objects that are seen are not real but literally mimic the real Forms. Accordingly. the outward "form" of a thing which we can see by our senses is not what it really is. In order to realize a thing of itself, we need to have a nearer look at the inward "form" of that thing. This is a case for Vietnamese Buddhism.